2011
DOI: 10.1002/mus.22204
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of MUNIX in patients with amyotrophic lateral sclerosis

Abstract: MUNIX has very good reproducibility in ALS patients. COV may exaggerate interoperator variation when MUNIX is very low. The higher variability in the thenar muscle is also due to variability in compound muscle action potential amplitude. Although both muscles show good reproducibility, the hypothenar is better suited for serial studies in individual patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 4 publications
6
58
1
1
Order By: Relevance
“…There are some arbitrary criteria imposed to accept a SIP. A motor unit size index can be similarly obtained by dividing the total CMAP by the MUNIX [48,49].…”
Section: Munixmentioning
confidence: 99%
“…There are some arbitrary criteria imposed to accept a SIP. A motor unit size index can be similarly obtained by dividing the total CMAP by the MUNIX [48,49].…”
Section: Munixmentioning
confidence: 99%
“…The coefficient of variation (COV)s of MUNIX were 14.3 (APB) and 13.6 (ADM), and furthermore COVs of MUSIX were 12.7 (APB) and 14.1 (ADM), within the acceptable range for healthy subjects. [2][3][4][5][6] In addition, the correlation coefficients of MUNIX and MUSIX values measured by the different operators were significant by applying the digital instrument ( Table 1, Fig. 1).…”
Section: Resultsmentioning
confidence: 91%
“…Previous studies have reported high reproducibility of MUNIX in a few muscles including the APB, ADM, fist dorsal interossei (FDI), biceps brachii (BB), tibialis anterior (TA), abductor hallucis (AH), nasalis and orbicularis oculi (OO) muscles, in healthy subjects or in patients with ALS. [2][3][4][5][6] Practically, the MUNIX would be influenced by the variability of CMAP amplitude, and furthermore the MUNIX depends on the SIP recorded during voluntary muscle contraction, a critical element of all MUNIX techniques. Therefore, MUNIX can be limited by unreliable SIP signals, which may not reflect the state of the motor neuron with fidelity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations